2002
DOI: 10.1161/01.cir.0000015605.30810.51
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous Left Atrial Appendage Occlusion (PLAATO) for Preventing Cardioembolism

Abstract: Background-Atrial fibrillation is associated with a high risk for cardioembolic stroke. The left atrial appendage (LAA) is the source of the vast majority of these thromboemboli. A novel implanted device for percutaneous LAA transcatheter occlusion (PLAATO) has been designed to seal the LAA. The purpose of this study was to test the feasibility and safety of transcatheter LAA occlusion in dogs. Methods and Results-A PLAATO implant was delivered to the LAA through a 12F transseptal catheter in 25 dogs. The PL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
78
0
1

Year Published

2002
2002
2019
2019

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 126 publications
(84 citation statements)
references
References 25 publications
5
78
0
1
Order By: Relevance
“…Several reports of preclinical data and human feasibility trials document successful endocardial application of implants and the possibility of stroke prevention. 14,15 In the first prospective, randomized trial of its type, the Embolic Protection in Patients with Atrial Fibrillation study showed that in patients with AF who were candidates for warfarin therapy, device closure of the LAA was associated with a reduction in hemorrhagic stroke risk compared with warfarin. All-cause stroke and all-cause mortality outcomes were noninferior to warfarin.…”
Section: Clinical Perspective On P 229mentioning
confidence: 99%
“…Several reports of preclinical data and human feasibility trials document successful endocardial application of implants and the possibility of stroke prevention. 14,15 In the first prospective, randomized trial of its type, the Embolic Protection in Patients with Atrial Fibrillation study showed that in patients with AF who were candidates for warfarin therapy, device closure of the LAA was associated with a reduction in hemorrhagic stroke risk compared with warfarin. All-cause stroke and all-cause mortality outcomes were noninferior to warfarin.…”
Section: Clinical Perspective On P 229mentioning
confidence: 99%
“…Studies in dogs demonstrated the ability of the device to seal the LAA. 5 We report our initial experience in humans.…”
mentioning
confidence: 99%
“…26,27 The PLAATO device consists of a self-expandable nitinol cage covered with an occlusive expanded polytetrafluoroethylene membrane ( Figure 1). The membrane occludes the orifice of the LAA but allows tissue incorporation into the device, and small anchors along the struts to assist with device anchoring and encourage healing.…”
Section: The Plaato Systemmentioning
confidence: 99%
“…26,28 Initial animal study and early clinical experience have shown the feasibility of the PLAATO procedure. 26,27 Recently, results of two concurrent feasibility studies that were conducted in Europe and North America were published. 28 The LAA occlusion was successful in 108 of 111 (97.3%) patients with nonrheumatic AF who were at high risk for ischemic stroke and not candidates for long-term OAC.…”
Section: The Plaato Systemmentioning
confidence: 99%